CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND FIRM FINANCIAL PERFORMANCE: THE CASE OF MINING AND NATURAL RESOURCES INDUSTRY IN INDONESIA - Dayanti, Nadia; W. Prihatiningtias, Yeney (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Business operations nowadays should not only pursue profits, but also contribute positively to the society as well as environment. This is because people currently have become more critical to the need of social control over the business. Business then has to respond this through the implementation of Corporate Social Responsibility (CSR) and disclose the activities related to it into the form of CSR disclosure. In line with this phenomenon, the purpose of this research is to examine the influence of CSR disclosure to firm financial performance. The legitimacy theory, the stakeholder theory as well as the agency theory are used in building the research framework in relation to CSR disclosure and its effect to firm financial performance. The study is conducted quantitatively by using natural resources and mining corporations listed in the Indonesian Stock Exchange from 2010-2012 as the samples. Meanwhile, the independent variable is CSR disclosure proxied by Corporate Social Disclosure Index (CSDI) and the control variables are firm financial performance represented by Return on Equity (ROE) and Cumulative Abnormal Return (CAR). Leverage, growth opportunities, firm size, and stock beta are used as control variables. To find out the relationship between the variables, the Ordinary Least Square (OLS) test is applied. Finally, the results indicate that the sign of the relationships are positive but not significant. This means that although the perspective that socially responsible firm may be associated with a set of economic benefits, it is now still emerging but now yet settled in the Indonesian context. Keywords: Corporate Social Responsibility Disclosure, Firm Financial Performance, Mining and Natural Resources Industry